Financial Socialisation and Promotion of Financial Inclusion, among Women Self-Help Group Members: An analysis - Prof. (Dr.) Sanjeeb K Jena, Dr. Somya Nanda (Journal of Informatics Education and Research, 2024)
India, a country of diversities has travelled a long way in the process of achieving inclusive growth through financial inclusion. The expedition has started from bank nationalisation in the year 1969 to flagship programs like SHG bank Linkage and PMDJY. Historically, women in India have faced various socio-economic challenges, including limited access to financial services and opportunities. To address these challenges and promote the financial inclusion of women, several initiatives and measures have been taken at the government, regulatory, and institutional levels. The PMJDY accounts have shown a remarkable growth in account openings. Around 50.09 Crore Jan Dhan accounts opened as of Aug 2023 where average deposits rise from Rs.1065 crore in 2015 to Rs.4087 Crore in 2023,nearly 3 times over Aug 2015. Around 56% of such accounts are owned by woman, whereas 67% of the accounts are owned by women in rural and semi urban areas (PIB 2023)[i]. But what is more discouraging is that India has the highest in inactive accounts which is 35% globally. In developing economies, women account owners are, on average, 5 percentage points more likely than men are inactive, in India the deviation is highest that is 12 %.Out of the women owned accounts, more than 32% are inactive. The usage of accounts also indicates a different saga as most of them is used for withdrawals of salary or wages, emergencies, or availing Govt. Benefits which leads to a lowering of financial inclusion among the women (Global Findex database 2021)[ii]. It's important to note that despite many advancements achieved by the country with respect to the financial inclusion of women through initiations like PMJDY, introduction of a range of women-centric financial products, such as savings accounts, fixed deposits, and insurance policies, often with special features and incentives, SHGs movements, development of digital financial ecosystem for women in rural areas to access financial services through mobile banking and digital wallets, undertaking financial literacy programs and campaigns aimed at women for improving their financial knowledge and decision-making capabilities, legal reforms related to property rights and inheritance rights, support for Women Entrepreneurs including access to credit, training, and mentorship, and by allocating funds specifically for women's welfare and empowerment through gender budgeting, the challenges still prevailing. The gender gap in financial inclusion still exist, with women in rural and marginalized communities facing more significant barriers. Social and cultural factors, limited financial literacy, and the persistence of gender-based violence in some regions were among the ongoing challenges (Fletschner & Kenney, 2011[iii]). The need for ongoing education and awareness programs, addressing gender biases, and expanding access to financial services in remote areas etc. remain the priorities of the policy makers. Achieving full financial inclusion for women in India requires a multi-faceted approach involving government policies, financial institutions, civil society organizations, and the active participation of women themselves. It is essential for both economic development and gender equality (Duflo, 2012[iv]; Bucciol et.al, 2022[v]).